Arthroscopic Parallel Double-Pulley Iliac Crest Bone Graft Fixation for Anterior Glenoid Reconstruction - Yan Xiong, M.D., Ph.D.; Li Yin, M.D., Ph.D.; Dongfa Liao, M.D.; Shuang Yang, M.D.; Weijie Yang, M.D.; Xiaolong Zheng, M.D.; Bing Deng, M.D., Ph.D. (Arthroscopy Techniques)
Glenoid bone defect is one major contributor to anterior shoulder instability. Numerous procedures have been developed for anterior glenoid reconstruction, such as the Eden-Hybinette procedure and the Latarjet-Bristow procedure, as well as various techniques for graft fixation, including screw, endobutton, and anchor fixation. However, these methods can be instrumentally and technically complex. This Technical Note introduces a arthroscopic technique using double-row suture anchors and parallel double-pulley to fix iliac crest bone grafts for anterior glenoid reconstruction, which enables convenient and quick fixation of the bone graft without requirement of any specialized instruments or consumables.